A critical analysis of regulated river ecosystem responses to managed environmental flows from reservoirs. (21st November 2014) - Gillespie, Ben R.; Desmet, Simon; Kay, Paul; Tillotson, Martin R.; Brown, Lee E.
Summary The flow regime of a river is fundamental in determining its ecological characteristics. Impoundment of rivers has been documented to severely impact the natural flow regime, resulting in abiotic and biotic changes in downstream ecosystems. Contemporary water legislation is driving increasing concern among environmentalists and water resource managers with respect to how these impacts can be mitigated. This has stimulated research aimed at assessing the relationship between reservoir outflow modification (i.e. managed environmental flows) and downstream ecosystem responses. We carried out a critical review and synthesis of the global literature concerning post‐impoundment reservoir outflow modification and associated downstream biotic and abiotic responses. Seventy‐six studies published between 1981 and 2012 were analysed. In contrast to previous studies of this subject, we systematically assessed the methodological quality of research to identify strengths and weaknesses of the approaches. We also undertook a novel quantification of ecosystem responses to flow modification, thus enabling identification of priorities for future research. We identified that: (i) there was a research bias towards North American and Western European studies; (ii) the majority of studies reported changes in flow magnitude (e.g. artificial floods) and primarily focused on traditionally monitored ecological groups (e.g. fish); (iii) relationships between flow, biota (e.g. macroinvertebrates) and water quality (e.g. electrical conductivity and suspended solids concentration) were evident, demonstrating the potential for managed environmental flows to manipulate river ecosystems; (iv) site‐specific factors (e.g. location, climate) are likely to be important as some ecosystem responses were inconsistent between studies (e.g. fish movement in response to increases in flow magnitude); and (v) quality of study design, methodological and analytical techniques varied, and these factors may have contributed to the reported variability of ecosystem response. To advance scientific understanding and guide future management of regulated flow regimes, we highlight a pressing need for: (i) diversification of study locations as well as flow modification and ecosystem response types assessed; (ii) a focus on understanding flow–ecosystem response relationships at regional scales; (iii) further quantitative studies to enable robust statistical analyses in future meta‐analyses; and (iv) robust monitoring of flow experiments and the use of contemporary statistical techniques to extract maximum knowledge from ecological response data.